Tensile Strength of Delta Variants in SARS-CoV-2 Spike Protein with Human ACE2 Receptor - Powrel, Jhulan (Butwal Campus Journal, 2024)
This research work aims to understand the mechanism by which SARS-CoV-2 and its variants bind to human body proteins in order to investigate their binding. Our research focuses on the tensile strength of spike protein mutated-RBD with human ACE2 in molecular level using molecular dynamics simulation via the approach of solving equations of motion. The method of steered molecular dynamics (SMD)is applied to study the strength of bonding interaction and tensile strength of two proteins. The present study is of delta variant using molecular dynamics. We have estimated the forces required for breaking the hydrogen bonds between SARS CoV-2 and hACE-2. The contact surface area between SARS CoV-2 and hACE-2 is found to be 875 Å2 and the tensile strength between the two protein is found to be 80 to 189 pN/ Å2.